Kinetics for the distribution of acrylamide in French fries, fried oil and vapour during frying of potatoes. (15th November 2016) - Hsu, Hui-Tsung; Chen, Ming-Jen; Tseng, Tzu-Ping; Cheng, Li-Hsin; Huang, Li-Jen; Yeh, Tai-Sheng
Highlights: Acrylamide formation in fried potato is distributed in three phases: French fries, frying oil, and air. Thermal decomposition of acrylamide is not significant during frying. Considering the total acrylamide amount in three phases, a lumped kinetic model was proposed. A high acrylamide level in air imply that occupational exposure to acrylamide via inhalation may be a hazard for fast-food workers. Abstract: Kinetic analysis for the formation of acrylamide in heated foods has been typically performed using only measured data of acrylamide in foods; however, its possible loss caused by release from heated foods into fried oil and air has seldom been considered. The results obtained from the monitoring of acrylamide by frying French fries indicated that acrylamide is distributed in three phases: French fries, frying oil, and air. From the evolved gas analysis of acrylamide and the measured concentration profile of the total acrylamide amount present in these phases, the kinetic behaviour for acrylamide formation does not obey the commonly used model of two-step consecutive reactions during frying, while a lumped kinetic model was proposed for the total acrylamide amount. Moreover, a high acrylamide level in air was observed, implying that, apart from consumers of French fries, fast-food restaurant workers are potentially subject to occupational hazards from acrylamide inhalation.